Truth and tradition: Bishop Mouneer Hanna Anis and the ongoing construction of Egyptian Anglican Orthodoxy - Gauvain, Richard (International journal for the study of the Christian church, 2024)
This article explores Bishop Mouneer Hanna Anis’ role in the Global South Fellowship of Anglican Churches (GSFA). Noting how Anis draws legitimacy from his position as the first Anglican Archbishop of the newly created Province of Alexandria, it examines his highlighting of the importance of North Africa, especially Egypt, in addressing contemporary challenges within the Global South. The article reflects on the innovative nature of Anis’ strategies in constructing a new narrative of Egyptian Anglican Orthodoxy. It describes Anis’ use of Thomas Oden’s historical analysis of the importance of early African contexts on the shaping of mature Christian tradition. And it notes the emphasis Anis places on Athanasius of Alexandria in constructing his narrative. By introducing several of Anis’ recent publications, the article also draws attention to key discussions (and disagreements) on the nature of the relationship between scripture and tradition within contemporary Global South settings.